The Estimation of Moulds Air Pollution in Tilda, Raipur - Lanjewar*, S. (Journal of Phytology, 2011)
<span style="font-size: 10pt; color: black; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">Aerobiological studies have received much attention recently because of applications in the field of allergy, dispersal of pathogens and in allied aspects of microbiology. Aerobiology is a branch of biology that deals with the study of the air borne organisms. <span style="font-size: 10pt; color: #403838; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN; mso-fareast-language: EN-IN; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';" lang="EN">The present study investigated the isolation and identification of airborne fungi from Tilda, Raipur. Air samples were taken by exposing a Petri dish with Potato dextrose agar medium for 15 min and after incubation the number of growing colonies was counted. The sampling procedure for fungi was performed 50 times at the research sites weekly during July 2009 to June 2010. A total of 312 fungal colonies were counted onÃ‚Â  Petri plates over a one year period. In total, some 26 mould species belonging to 15 genera were isolated. Alternaria alternata, Cladosporium and Aspergillus species were the most abundant species in the study area (13.66, 5.80 and 5.50% of the total, respectively).